Complement C3 Affects Rac1 Activity in the Developing Brain - Gorelik, Anna; Sapir, Tamar; Ben-Reuven, Lihi; Reiner, Orly (Frontiers in Molecular Neuroscience, 2018)
The complement system, which is part of the innate immune response system, has been recently shown to participate in multiple key processes in the developing brain. Here we aimed to elucidate downstream signaling responses linking complement C3, a key molecule of the pathway, to small GTPases, known to affect the cytoskeleton. The expression pattern of the activated small GTPase Rac1 resembled that of complement C3. C3-deficient mice exhibited reduced Rac1 and elevated RhoA activity in comparison with control mice. The most pronounced reduction of Rac1 activity occurred at embryonic day 14. Rac1 has been implicated in neuronal migration as well as neuronal stem cell proliferation and differentiation. Consistent with the reduction in Rac1 activity, the expression of phospho-coffilin, decreased in migrating neurons. Reduced Rac1-GTP was also correlated with a decrease in the expression of progenitor markers (Nestin, Pax6 and Tbr2) and conversely the expression of neuronal markers (Dcx and NeuN) increased in C3 knockout cortices in comparison with wild-type cortices. More specifically, C3 deficiency resulted in a reduction in the number of the cells in S-phase and an elevation in the number of cells that precociously exited the cell cycle. Collectively, our findings suggest that C3 impacts the activity of small GTPases resulting in cell cycle defects and premature neuronal differentiation.